HUBUNGAN KOMPETENSI, MOTIVASI BERPRESTASI DAN FASILITAS KERJA WIDYAISWARA DENGAN KUALITAS PELAYANAN WIDYAISWARA DALAM PENYELENGGARAAN PENDIDIKAN DAN PELATIHAN (DIKLAT) DI PPPPTK BIDANG BANGUNAN DAN LISTRIK MEDAN - Purba, Jintohidro; Napitupulu, Efendi; Sinaga, Dearlina (LPPM Universitas Darma Agung, 2020)
Service quality is a comparison between the training participants' perceptions of the real services they receive with the services they actually expect. The problems that occur are that the training held is not fully able to answer the competency needs of the future, the training is not able to achieve the desired effectiveness, and the concept of measuring the benefits of training that stops at the satisfaction of training participants has not yet touched community satisfaction. This study aims at finding the relationship among competence, achievement motivation and work facilities partially and simultaneously with the service quality of “widyaiswara” in the implementation of education and training (Diklat) in PPPPTK in the Field of Building and Electricity Medan. The population of this research is 53 “widyaiswara” people. To determine the number of samples, the Slovin formula is used so that the sample amounted to 35 people. Data collection techniques in this study are questionnaires, interviews and documentation studies while the data analysis technique used is the classical assumption test, correlation analysis, partial test, simultaneous test and the coefficient of determination. The results show that the competency variable had a positive and significant relationship with the service quality of “widyaiswara” at PPPPTK in the Field of Building and Electricity Medan. The achievement motivation variable has a positive and significant relationship with the service quality of the “widyaiswara” at PPPPTK in the Field of Building and Electricity Medan. The work facility variable has a positive and significant relationship with the service quality of the “widyaiswara” at PPPPTK in the Field of Building and Electricity Medan. The competency variables, achievement motivation and work facilities simultaneously have a significant relationship with the service quality of the “widyaiswara” at PPPPTK in the Field of Building and Electricity in Medan. The coefficient of determination is 91.90%, variations in service quality can be explained by simultaneous competence, achievement motivation and work facilities, while the remaining 7.10% is explained by other factors, such as variables of discipline and leadership. It is suggested that “Widyaiswara” need to improve competence to cooperate among fellow “widyaiswara” and always actively motivate the training participants to be able to achieve the predetermined goals of the education and training. “Widyaiswara” needs to increase achievement motivation with a strong desire to be the best and always try new innovations in learning. Institution leaders need to repair work facilities by paying attention to damaged facilities, as well as providing adequate transportation support for “widyaiswara” while on duty outside the office in the official. Further research is needed by other researchers by using more independent variables outside the independent variables that have been studied in this study to obtain a relationship with the variable service quality.